In their narratives: academic socialization in the experience of sensory processing sensitivity among university students - Saglietti, Marzia; Marini, Mara; Livi, Stefano (Frontiers in Psychology, 2024)
While much of the worldwide contemporary research on sensory processing sensitivity (SPS) and environmental sensitivity (ES) has relied on the participation of university students, there remains a significant gap in understanding the academic social experiences of those scoring high in SPS (i.e., highly sensitive individuals). To address this gap, this exploratory study aimed to investigate in detail students’ academic socialization through their narratives. We conducted nine interviews with Italian university students who self-identified as highly sensitive based on the Highly Sensitive Person Scale (Aron & Aron, 1997). Through thematic reflexive analysis (Braun & Clarke, 2006, 2022), we identified and analyzed 12 themes concerning their self-definitions, their university experience (at lectures, before, during, and after exams), and their socialization with peers and teachers. After 20 years of research on SPS, this study integrates the relevant literature into the field of social psychology and academic socialization, emphasizing the importance of understanding SPS within real-life educational contexts and considering highly sensitive students’ perspectives on their resources and challenges in attending university. By contributing to the emerging qualitative literature on SPS and ES, this study provides practical implications for educators and policymakers seeking to foster inclusive learning environments for all students.